Analisis Kesalahan Penggunaan Tanda Baca dalam Penulisan Akademik Mahasiswa - Ibrohim Ibrohim; Agung Pranoto Kadiatmaja (Indo Publishing, 2026)
This study aims to analyze punctuation errors in students' academic writing. Proper use of punctuation is essential in conveying clear and precise meaning in academic texts. However, many students still make errors in applying punctuation marks according to standardized Indonesian language rules. This research employed a descriptive qualitative method. The data were collected from students' academic papers, including essays and reports, using documentation and note-taking techniques. The analysis focused on identifying, classifying, and interpreting punctuation errors based on linguistic error analysis theory. The results showed that the most frequent errors occurred in the use of commas, periods, and hyphens. These errors were caused by a lack of understanding of punctuation rules, interference from spoken language, and limited writing practice. The findings indicate that improving students’ writing skills requires more emphasis on teaching punctuation rules and providing consistent writing exercises. In conclusion, punctuation errors remain a significant issue in students' academic writing and need systematic attention in language learning.